Effects of column damage on the reliability of reinforced concrete portal frames - Kernou Nassim; Lydia Messaoudene; Lyacine Bennacer (Građevinar)
The reliability and behaviour of columns belonging to portal-reinforced concrete frames depend on many factors. This paper presents a parametric study of a reliability column in a non-linear domain, considering mechanical variability and targeting damaged areas of the reinforced concrete columns. In this study, an adaptive method for assessing the reliability of columns with respect to damage states is proposed. The method is an indirect coupling of the response surface and finite element model in the non-linear domain. The main goal of this study was to provide a structural engineer with a modelling approach for optimal and robust column design. The results of the present study show that the reliability of columns belonging to portal frames is closely related to the quality of the constituent materials (steel and concrete) and the type of load applied. The reliability of this type of column also decreases with increasing load and applied displacement and increases with increasing compressive strength and yield strength of the steel. The uncertainties associated with the structural models are considered, with their impact on structure reliability studied using a sensitivity analysis, which allows the proposed approach to make the best possible decision for a better design and, therefore, good behaviour under different parameters.